Menilik Perkembangan Pemikiran Politik Islam Masa Modern (Sebuah Pembacaan Awal) - Muhammad Zulkifli Butarbutar; Karmila Damanik; Marzuki (Medan Resource Center, 2022)
Reading of modern Islamic political thought based on ijtihad The reformer will be able to lay the foundation of history as well as read critical of the current political situation. Through the study of the mind some figures, modern Islamic political thought tends to be dominated by symptoms of fundamentalism. However, after scholars developed some In the aspect of study, modern Islamic political thought seems to be the starting point choice of state by Muslims. Paradigm of “symbiosis” between teacher and student This then offers enlightenment for the current state of affairs.